Wage Rates of Agricultural Labourers in Kerala - A. V. Jose (Economic and Political Weekly, Vol. 8, No. 4/6, Annual Number (Feb., 1973), 1973)
According to a comparative study of wage rates in the IADP districts in various states between 1962- 63 and 1967-68, the daily wage rate for agricultural lab>ourers recorded the maximum percentage increase in the Alleppey and Palghat districts of Kerala, although the growth of agricultural production associated with the green revolution has been much greater in the IADP districts of other states like Punjab, Tamil Nadu and Gujarat. This article examines the level, fluctuation and trend of wage rates for agricultural workers in the whole of Kerala to see to what extent the phenomenon observed in the two IADP districts obtained in the other districts of the state. The two main findings that emerge from this study are, first, that the rise in the real wage rate in Kerala between 1960-61 and 1967-68 was far lower than indicated by earlier studies; and, second, that there were substantial variations between different villages in the long-term movement of real wage rates; in some the real wage rates had declined.